PEMBERLAKUAN WORK FROM HOME (WFH) DAN DAMPAK EKONOMINYA BAGI PENGEMUDI OJEK ONLINE - Edy Edy; Uun Novalia Harahap (Jurnal Simetri Rekayasa, 2020)
The Government of the Republic of Indonesia has established the COVID-19 pandemic as a National Disaster. The government requested that the community conduct social distancing in order to prevent the transmission of Corona Virus or COVID-19. Activities that are usually done outside the home, such as work, study and worship can be carried out inside the house (work from home). The application of social distancing (work from home) has an economic impact on people whose daily income is one of them being an online motorcycle taxi driver. From the research results obtained the application of social distancing (work from home) causes a decrease in online motorcycle taxi driver activity with a percentage ranging from -16.7% to -80.0% with an average value = -57.58%. The decline in activity caused a decrease in online motorcycle taxi driver acceptance with percentages ranging from -5.3% to -87.5% with an average value of -58.14%.